2019
DOI: 10.1016/j.jmbbm.2019.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Voxel-based micro-finite element analysis of dental implants in a human cadaveric mandible: Tissue modulus assignment and sensitivity analyses

Abstract: The success of dental implant treatment is related to the complex 3-dimensional (3D) biomechanics of the implant-bone interaction. In this work, 3D numerical models are built based on micro X-ray computed tomography (micro-CT) images of a cadaveric mandible specimen with implants placed in it. The simulation results show that the computed strain values in bone are sensitive to the uncertainties in trabecular tissue modulus and fairly insensitive to the modulus of implants and teeth and the detailed geometry of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…Furthermore, parameters related to the construction of the model reported heterogeneity, which could be associated with the evolution of technologies. The development of tomography has been sped up since the last decades, and this imaging procedure is now reported as being one of the most relevant techniques for recording accurate volumes in dentistry [ 9 , 13 , 15 ], thus defining a precise FE model [ 46 ]. Interestingly, the number of elements seems to have increased progressively in function of the rise in computing capacity, but it is of note that under half of the studies reported to have used a convergence test.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, parameters related to the construction of the model reported heterogeneity, which could be associated with the evolution of technologies. The development of tomography has been sped up since the last decades, and this imaging procedure is now reported as being one of the most relevant techniques for recording accurate volumes in dentistry [ 9 , 13 , 15 ], thus defining a precise FE model [ 46 ]. Interestingly, the number of elements seems to have increased progressively in function of the rise in computing capacity, but it is of note that under half of the studies reported to have used a convergence test.…”
Section: Discussionmentioning
confidence: 99%
“…Finite element (FE) models have been widely used to model the implant biomechanical behavior at the organ scale in the context of primary and secondary stability, but often the BII is modeled as a perfect interface, i.e., continuity of stresses and displacements at the interface [19]. In particular in the context of dental implantology, microfinite element analyses were applied to images obtained using X-ray micro-computed tomography [20, 21], which allowed to assess the strain and stress field around the implant. However, the BII was often considered as fully bonded.…”
Section: Introductionmentioning
confidence: 99%
“…Optical microscopy techniques are often used to observe biological tissues, but they consist in analysing two-dimensional sections. To improve such analysis, three-dimensional techniques have been developed such as X-ray μCT [148,149], which allows imaging of woven bone formation at a titanium interface at the microscale [150] for further finite-element analysis at the microscopic level [151].…”
Section: X-ray-based Techniquesmentioning
confidence: 99%